Intravitreal properties of porous silicon photonic crystals: a potential self-reporting intraocular drug-delivery vehicle. Issue 5 (25th April 2008) - Cheng, L; Anglin, E; Cunin, F; Kim, D; Sailor, M J; Falkenstein, I; Tammewar, A; Freeman, W R
Abstract : Aim: To determine the suitability of porous silicon photonic crystals for intraocular drug-delivery. Methods: A rugate structure was electrochemically etched into a highly doped p-type silicon substrate to create a porous silicon film that was subsequently removed and ultrasonically fractured into particles. To stabilise the particles in aqueous media, the silicon particles were modified by surface alkylation (using thermal hydrosilylation) or by thermal oxidation. Unmodified particles, hydrosilylated particles and oxidised particles were injected into rabbit vitreous. The stability and toxicity of each type of particle were studied by indirect ophthalmoscopy, biomicroscopy, tonometry, electroretinography (ERG) and histology. Results: No toxicity was observed with any type of the particles during a period of >4 months. Surface alkylation led to dramatically increased intravitreal stability and slow degradation. The estimated vitreous half-life increased from 1 week (fresh particles) to 5 weeks (oxidised particles) and to 16 weeks (hydrosilylated particles). Conclusion: The porous silicon photonic crystals showed good biocompatibility and may be used as an intraocular drug-delivery system. The intravitreal injectable porous silicon photonic crystals may be engineered to host a variety of therapeutics and achieve controlled drug release over long periods of time to treat chronic vitreoretinal diseases.